2022
DOI: 10.1108/ijwhm-04-2021-0105
|View full text |Cite
|
Sign up to set email alerts
|

The economic impact of workplace physical activity interventions in Europe: a systematic review of available evidence

Abstract: PurposeThere is growing interest in the economic impact of workplace physical activity interventions, but the evidence is still lacking — especially in Europe. Although, some evidence on the return on investment (ROI) is found in literature, the included studies may not be applicable to the Europe situation. Therefore, the objective of this study was to review current evidence on the economic impact of workplace physical activity interventions in European countries.Design/methodology/approachA systematic revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
(246 reference statements)
0
4
0
Order By: Relevance
“…Similarly, a Swiss study found an effect of an IPET inspired intervention on neck pain-related work productivity, as well as a weekly saved cost of CHF 27.40 per participant, and concludes that the intervention could reduce the economic burden of neck pain among office workers [ 26 ]. However, regarding economic evaluation of workplace physical activity interventions in general, two systematic reviews recently pointed out that such evidence is inconsistent, due to large heterogeneity in such studies [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a Swiss study found an effect of an IPET inspired intervention on neck pain-related work productivity, as well as a weekly saved cost of CHF 27.40 per participant, and concludes that the intervention could reduce the economic burden of neck pain among office workers [ 26 ]. However, regarding economic evaluation of workplace physical activity interventions in general, two systematic reviews recently pointed out that such evidence is inconsistent, due to large heterogeneity in such studies [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies did not find a statistically significant effect of WPA programmes on absenteeism (Hartfiel et al, 2017). Braun et al (2022) also failed to prove the effectiveness of WPA programmes on self-assessed productivity and job satisfaction. In their systematic review, three studies found a positive effect of WPA on the financial return of the employer compared to four studies that did not find any effect.…”
Section: Workplace Physical Activitymentioning
confidence: 97%
“…However, some studies did not find a statistically significant effect of WPA programmes on absenteeism (Hartfiel et al ., 2017). Braun et al . (2022) also failed to prove the effectiveness of WPA programmes on self-assessed productivity and job satisfaction.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The third study was a costing analysis of an incentivised workplace physical activity intervention to increase daily steps among inactive employees (Mason et al, 2018). The fourth paper was a systematic review assessing the economic impact of workplace physical activity interventions in Europe (Braun et al, 2022).…”
Section: Healthy Eating and Physical Activitymentioning
confidence: 99%